2013
DOI: 10.1007/s11270-013-1645-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pseudomonas fluorescens Seed Bioinoculation on Heavy Metal Accumulation for Mirabilis jalapa Phytoextraction in Smelter-Contaminated Soil

Abstract: Some Pseudomonas fluorescens strains, consistently isolated from the rhizosphere of wild plants grown in a soil that was highly polluted with illegal waste of smelter residues, were utilised for Mirabilis jalapa seed bioinoculation to verify their effects on seed germination and on promoting a higher heavy metal accumulation in the plant rhizosphere and/or uptake in the leaves. The high content of heavy metals in the soil induced a decrease in either the leaf dry weight or photosynthetic pigment concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
(61 reference statements)
2
5
0
Order By: Relevance
“…Therefore, the response of the heavy metal speciation distributions to plant species must be further studied to confirm these findings. Nevertheless, we found that the contents of Zn and Cd in the rhizosphere of AA was significantly lower than CK at S1, which is consistent with the findings of Inelova et al (2021) and Petriccione et al (2013), who found that A. annua has a large accumulation capacity for heavy metals, especially Cd and Zn. Note that the difference among the heavy metal content among the three plant species at S2 was mainly attributable to differences in sampling location rather than the effect of plant species because C. breviculmis was growing closer to S1 than the other plants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the response of the heavy metal speciation distributions to plant species must be further studied to confirm these findings. Nevertheless, we found that the contents of Zn and Cd in the rhizosphere of AA was significantly lower than CK at S1, which is consistent with the findings of Inelova et al (2021) and Petriccione et al (2013), who found that A. annua has a large accumulation capacity for heavy metals, especially Cd and Zn. Note that the difference among the heavy metal content among the three plant species at S2 was mainly attributable to differences in sampling location rather than the effect of plant species because C. breviculmis was growing closer to S1 than the other plants.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, some metal-tolerant plants have been the focus of previous studies (Becerra-Castro et al, 2012;Elbehiry et al, 2020) because of their biological mechanisms that resist and tolerate heavy metals. Pseudo-metallophyte populations of Carex breviculmis (Lei and Duan, 2008;Xu et al, 2020), Buddleja davidii (Margui et al, 2006), and Artemisia annua (Petriccione et al, 2013;Inelova et al, 2021) are metal-tolerant plant species that have exhibited good abilities in colonizing Pb, Zn, and Cd contaminated soils. Soil microorganisms play an important role in maintaining soil quality and function by decomposing organic matter, participating in nutrient cycling, and reducing heavy metal toxicity (Banning et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why plant response to bioinoculants is not always positive, despite inoculants often undergoing rigorous testing during development. Most bioinoculants are developed and marketed to affect target hosts directly, either by establishing a functional symbiosis with the host itself, or by reducing stress (Khan et al, 2011;Petriccione et al, 2013;Kuan et al, 2016;Singh et al, 2019). Our results suggest that inoculum development should include interactions with resident communities in order to both create more robust bioinoculants and guard against potential risks to resident SMC.…”
Section: Does Inoculation Affect Plant Performance?mentioning
confidence: 82%
“…While P. fluorescens was more effective in increasing Cd concentration in maize shoot and improving Cd phytoextraction efficiency. It has been reported that Cd concentration in the rhizosphere of Mirabilis jalapa inoculated with P. fluorescens strains significantly increased as compared with that of non-inoculated plants (Petriccione et al, 2013). Inoculation with P. fluorescens and/or a combination of P. fluorescens and P. indica noticeably increased mean Cd concentration in maize shoot but had no significant effect on mean Cd uptake in maize shoot.…”
Section: Discussionmentioning
confidence: 99%